Effects of health education on physical activity promotion based on precede-proceed model among adolescents in Yunnan, China - Linxian, Zeng (2025)
Regular physical activity is crucial for adolescent growth, while a lack of it can harm development. The PRECEDE-PROCEED model is a widely used health promotion framework that focuses on psychological and social factors. The model consists of two phases: PRECEDE (assessment) and PROCEED (implementation and evaluation), with a total of nine steps. In the PRECEDE phase, through five assessment steps, a comprehensive analysis of factors affecting health behavior is conducted, summarizing susceptible factors (attitudes and beliefs), reinforcing factors (social support), and enabling factors (resources and policies). In the PROCEED phase, targeted intervention programs are designed, implemented, and evaluated. This study followed the nine steps of the PRECEDE-PROCEED model and was conducted in three phases: two cross-sectional studies followed by a randomized controlled trial. In Phase 1, the researchers used cluster random sampling to select the participants. The reliability and validity of several physical activity-related questionnaires (ASAFA-C, Q-SPACE-C, EBBS-CN, PASES-C, and PAQ-CN) were tested using confirmatory factor analysis and internal consistency reliability. A total of 625 questionnaires were collected, with 586 valid responses (49.8% male, 50.2% female). Data analysis was done using Mplus 8.0 and SPSS 29.0, confirming that all models had good fit within acceptable ranges. These results validated the questionnaires as reliable tools for assessing adolescent physical activity in Yunnan Province. In Phase 2, cluster random sampling resulted in 1,250 completed questionnaires, with 920 valid responses (51.2% male, 48.8% female). SPSS 29.0 was used to analyse factors influencing adolescent physical activity, including social support, self-efficacy, exercise benefits/barriers, school environment, physical fitness, and activity levels. The results showed that physical activity level was insufficient, their physical fitness was at a passing level, and the other factors were at a moderate level among adolescents (high school students) in Yunnan Province, China. SEM confirmed significant relationships between these factors, with good model fit indices (RMSEA (90% CI) = 0.029 [0.026, 0.033], CFI = 0.981, TLI = 0.979, SRMR = 0.031). In Phase 3, a 12-week health education program was developed, combining lectures with physical activity. The intervention included 45-minute interactive learning sessions and 45-minute physical activities, with parents participating in two sessions. A total of 156 high school students participated, with the intervention group (n=79) and control group (n=77). Participants completed questionnaires and physical fitness tests at four points: before the intervention, during the 4th and 8th weeks, and after the program. Data analysis using SPSS 29.0 and Mixed ANOVA showed that the intervention group had significantly higher scores in social support, self-efficacy, exercise benefits, physical fitness, and physical activity levels. They also had lower scores in exercise barriers and school environment limitations compared to the control group. The study concluded that the validated measurement tools effectively assess adolescent physical activity, and the PRECEDE-PROCEED-based health education program successfully improved key factors influencing physical activity participation among high school students in China. Although this study provides valuable insights, it is important to note that the sample was geographically limited, which may affect the generalizability of the results